P3.305 Vulnerability of Sex Workers (SWs) and Their Particular Needs For HIV/STI Prevention, Diagnosis, and Treatment: BORDERNETwork Research Findings and Recommendations For Comprehensive Sexual Health Response. (13th July 2013) - Steffan, E; Netzelmann, T Arsova; Lõhmus, L; Kalikov, J; Karnite, A; Leffers, A; Kucharova, B; Dimitrova, R; Fierbinteanu, C
Abstract : Background: Prostitution is a frequent and often controversial discussion topic at expert and political levels in Europe. Still evidence-based knowledge of sex work in general, and the situation of the SWs in particular, is scarce. BORDERNETwork addressed these gaps with an integrated bio-behavioural survey in seven EU countries. It compiled contextualised knowledge on the health and social situations of SWs, detected prevalence of and vulnerability to HIV/STIs, and formulated prevention practise recommendations. Methods: Behavioural and epidemiological data was collected between March 2011 and February 2012 through qualitative face-to-face interviews (an 85-item questionnaire) and blood screening tests (HIV, Syphilis, HCV, and HBV) among 956 SWs (respondents- and service-driven sample) in six capital cities and a border area. Results: The findings outlined multiple risks: About 38% of the SWs had experience injecting drugs, 60% lacked health insurance. 59% had had an HIV test in the past year, but STI/sexual health services are hardly utilised. 77.1% had not attended an STI-specialist and 51.1% had not visited a gynaecologist in the past year. The prevalence for HIV was 4.6%, for Syphilis - 4.5%, for Hepatitis B - 6.2%, and for Hepatitis C - 24% (over 90% among PWID). Risk predictors linked in particular to increased prevalence of Syphilis, HBV, and HCV were drug and alcohol use before/during sex work and inconsistent condom use during oral/vaginal sex with clients. Conclusions: The behavioural and social determinants of risk, including precarious living conditions and stigma, multiply the vulnerability of SWs impeding their access to health and social care. To that end policy regulations should endorse the creation of structures for early and easy access to health services. An adequate health care provision package (incl. sexual health) should be envisaged including those SWs lacking health, social insurance and legal status in the country of stay also.